2021
DOI: 10.1016/j.isci.2021.102935
|View full text |Cite
|
Sign up to set email alerts
|

A persistent invasive phenotype in post-hypoxic tumor cells is revealed by fate mapping and computational modeling

Abstract: Hypoxia is a critical factor in solid tumors that has been associated with cancer progression and aggressiveness. We recently developed a hypoxia fate mapping system to trace post-hypoxic cells within a tumor for the first time. This approach uses an oxygen-dependent fluorescent switch and allowed us to measure key biological features such as oxygen distribution, cell proliferation, and migration. We developed a computational model to investigate the motility and phenotypic persistence of hypoxic and post-hypo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Our computational model was implemented leveraging the previously developed PhysiCell ( Ghaffarizadeh et al., 2018 ) (physics-based multicellular simulator), an agent-based simulator that models the interaction between cells and diffusing fields in dynamic tissue microenvironments. Below we provide a very brief overview of the PhysiCell software and direct the reader to physicell.org and the following publications for more information ( Ghaffarizadeh et al., 2018 ; Ozik et al., 2018 ; Rocha et al., 2021 ; Wang et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our computational model was implemented leveraging the previously developed PhysiCell ( Ghaffarizadeh et al., 2018 ) (physics-based multicellular simulator), an agent-based simulator that models the interaction between cells and diffusing fields in dynamic tissue microenvironments. Below we provide a very brief overview of the PhysiCell software and direct the reader to physicell.org and the following publications for more information ( Ghaffarizadeh et al., 2018 ; Ozik et al., 2018 ; Rocha et al., 2021 ; Wang et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this system, cells that experience hypoxia maintain permanent eGFP expression. Our studies showed a correlation of eGFP, Hypoxyprobe™, and HIF-1α expression in IF-labeled tissue sections of orthotopic tumors harvested from the mammary fat pad of mice [ 19 , 69 ]. Furthermore, the system allowed us to image and collect cells that experienced hypoxia in the primary tumor and metastasized to distant organs such as the lung and liver [ 19 , 70 ].…”
Section: Detection Of Hypoxia In Vivomentioning
confidence: 99%
“…Activation of hypoxia-inducible factors (HIFs) is an important response of cells at low oxygen concentrations. Three heterodimeric factors (HIF-1, HIF-2, and HIF-3) composed of oxygen-sensible alpha units and stable beta units, are described in the literature [ 4 , 5 ]. In physiological conditions, HIF-1a and HIF-2a are proteasomally degraded.…”
Section: Introductionmentioning
confidence: 99%
“…In hypoxic conditions, HIF-1a and HIF-2a are directed in the cellular nucleus and dimerize with HIF-1β. HIF-1 and HIF-2 are expressed in many tissues and regulate the expression of more than 1000 genes involved in hypoxia [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%